PENGARUH MODEL PEMBELAJARAN TALKING STICK BERBANTUAN MEDIA TONGKAT AJAIB TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK TEMA LINGKUNGAN SAHABAT KITA KELAS V SD NEGERI 107461 DESA PAYA LOMBANG - Rita Dwi Yanti; Umar Darwis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of the talking stick learning model assisted by magic stick media on student learning outcomes in thematic learning on the environmental theme of our friends in class V of SD Negeri 107461 Paya Lombang Village. This research uses quasi-experimental research with a pretest-posttest control group research design. The data collection technique in this research is a written test. The population in this study were all fifth grade students at SD Negeri 107461 Paya Lombang Village, totaling 38 students with sampling using random sampling. The research results showed that the average posttest score for the experimental group was 74.44 (good category) which was higher than the average posttest score for the control group, namely 62 (fair category). Based on the results of the t-test, the calculated t value was 1.9447 which was greater than the t table, namely 1.6882 (1.9447 > 1.6882). Based on the results of the t-test, it showed that there was an influence on the talking stick learning model assisted by magic stick media. on student learning outcomes in thematic learning on the environmental theme of our friends class V at SD Negeri 107461 Paya Lombang Village for the 2023/2024 academic year.